2018
DOI: 10.1016/j.schres.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Thought, language, and communication deficits and association with everyday functional outcomes among community-dwelling middle-aged and older adults with schizophrenia

Abstract: Older adults with schizophrenia experience poorer community integration and social functioning compared to same-age peers with no mental health disorders; these individuals are at elevated risk for functional decline and early institutionalization in long-term care facilities. Deficits in thought, language, and communication (TLC; that is, thought disorder and alogia) are core features of schizophrenia and may worsen with age; however, little research focuses on the functional sequelae of these impairments amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
0
12
0
2
Order By: Relevance
“…More recent research has continued to corroborate these findings. For example, it has been demonstrated that deficits in thought, language and communication domains are associated with worse functional outcomes, including occupational functioning, ability to communicate effectively in social situations, and general community functioning [ 73 ]. Difficulties interpreting verbal cues like humor and emotional prosody [ 74 ] as well as visual cues like facial emotion [ 75 ] have been linked with poor social communication and functioning in psychosis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recent research has continued to corroborate these findings. For example, it has been demonstrated that deficits in thought, language and communication domains are associated with worse functional outcomes, including occupational functioning, ability to communicate effectively in social situations, and general community functioning [ 73 ]. Difficulties interpreting verbal cues like humor and emotional prosody [ 74 ] as well as visual cues like facial emotion [ 75 ] have been linked with poor social communication and functioning in psychosis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2007, Muralidharan et al . 2018); there are increased rates of depression and anxiety amongst adolescents with SLCN that sustains into adulthood (Botting et al . 2016); and SLCN are evident in individuals with dementia (Bailey et al .…”
Section: Communication and Rough Sleepingmentioning
confidence: 99%
“…In a school setting, it can be difficult to “fit in” and develop friendships, owing to the magnitude of stressors. Socially expected roles of youth may be delayed or even avoided by young persons diagnosed with schizophrenia, with prominent isolating behaviors that can continue into older adulthood (Muralidharan, Finch, Bowie, & Harvey, 2018; Ogden, 2014a; Strugstad et al, 2018).…”
Section: Elder’s Life Course Theorymentioning
confidence: 99%